Plasma endogenous enkephalin levels in early systemic sclerosis: clinical and laboratory associations - McNearney, T.A. (2010)
OBJECTIVE: Met- and leu-enkephalins are endogenous opioid neuropeptides with potent analgesic, vasoactive, immunomodulatory and anti-apoptotic properties. We hypothesised that clinical or immunological variables of early systemic sclerosis (SSc) might be correlated to plasma enkephalin levels. METHODS: Plasma samples were collected at study entry of the Genetics versus Environment in Scleroderma Outcomes Study (GENISOS) cohort (early SSc, n=116). Plasma met-enkephalin and leu-enkephalin levels (ug/ml) were measured by high performance liquid chromatography (HPLC) and correlated to clinical and laboratory parameters in the GENISOS database. Statistical analyses were performed by nonparametric Wilcoxon rank sum tests and Pearson correlation coefficients. RESULTS: Significantly lower plasma met-enkephalin levels were associated with anti-topoisomerase-I seropositivity (6+8.3 vs. 14.9+22.8 ug/ml, p=0.02). Plasma leu-enkephalin levels were significantly higher in SSc patients with digital pulp loss (95.6+130 vs. 64.9+101 ug/ml, p=0.02). Lower mean plasma met-enkephalin levels and inversely higher leu-enkephalin levels were noted in SSc patients with Raynaud’s phenomena (p=NS). CONCLUSION: The associations of plasma enkephalin levels to immunologic or clinical pathologies may underscore their vasogenic or fibrogenic significance and potential as therapeutic targets in early SSc.